GAMBARAN HASIL BILIRUBIN INDIRECT PADA BAYI UMUR 0-14 HARI DI RUMAH SAKIT GADING MEDIKA KOTA BENGKULU - Mardiyansyah Bahar; Sherly Irga Melani; Yurman Yurman (Journal of Indonesian Medical Laboratory and Science, 2023)
Jaundice is the result of increased levels of indirect ("unconjugated") bilirubin or direct ("conjugated") bilirubin levels in the blood. Indirect bilirubin does not function because while still in the womb, the fetus needs a lot of red blood cells, because the baby's lungs have not functioned perfectly, so the baby has not been able to process indirect bilirubin into direct bilirubin in the liver so that it can be excreted through feces and urine. Jaundice is a yellow discoloration of the skin, mucous membranes, and sclera caused by increased bilirubin production in the blood. The purpose of this study was to determine the picture of the results of indirect bilirubin examination in infants aged 0-14 days at Gading Medika Hospital in Bengkulu City. The research method used is descriptive quantitative analytics. This research was conducted at Gading Medika Hospital. The samples used were 42 samples Data analysis techniques are descriptive. The results of the study from 42 samples of infants who carried out indirect bilirubin examination were an increase with all the results of testing high indirect bilirubin levels in infants aged 0-14 days in 2022 at Gading Medika Hospital in Bengkulu City.